Orientation of Islamic Education Materials in Indonesia: An Overview of the Typology of Approaches - Rohman Rohman (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2026)
These dynamics have given birth to diverse paradigms in the construction and implementation of PAI materials, each reflecting a different understanding of the relationship between Islamic teachings and educational goals. This study aims to analyze the typology of Islamic Religious Education material in Indonesia and examine its implications for the development of contemporary Islamic education. This research uses a qualitative approach with the library research method. Data was collected from books, journal articles, scientific papers, and various documents relevant to Islamic education thinking and the development of Islamic Religious Education materials. Data was analyzed through content analysis and critical-interpretive approaches to identify the dominant paradigm underlying Islamic Religious Education material. The results of the study show that there are five main typologies of Islamic Religious Education materials in Indonesia. First, a formalistic typology that emphasizes the transmission of religious norms, legal doctrines, and Islamic symbols as the basis of the educational process. Second, a substantivistic typology that prioritizes the internalization of Islamic universal values such as justice, tolerance, humanity, and social welfare rather than symbolic religious expressions. Third, a transformative typology that views Islamic Religious Education as an instrument of social change with an emphasis on critical awareness, liberation, and social responsibility. Fourth, a totalistic typology that views Islam as a comprehensive system that covers all aspects of life and seeks to integrate Islamic principles into every dimension of education. Fifth, an idealistic typology that emphasizes the realization of